Bioactive peptides from food : sources, analysis, and functions - Nollet, Leo M. L., 1948-; Ötleş, Semih (CRC Press, Taylor & Francis Group, 2022)
"Bioactive peptides, present in foods, can exert several beneficial effects like preventing diseases or modulating the physiological systems once they are absorbed in the human body. Methods of isolation of these peptides from different protein sources with their in vitro and vivo physiological effects are addressed in this book, as is an overview of the different analysis methods. The book also includes a discussion of health benefits, such as antimicrobial, antiallergic, antihypertensive, antitumor, and immunomodulatory properties of peptides"- Resumé vydavatel
Keywords: peptidy; biologicky aktivní látky; analýza potravin; peptids; bioactive compounds; food analysis; sborníky; papers of several authors